Technology and smallholders: helping farmers to future-proof crops with satellite data and high-tech seeds. - Amarnath, Giriraj (CGIAR Research Program on Water, Land and Ecosystems, 2019)
Over 750 million people in South Asia are vulnerable to natural disasters. Climate change - induced factors such as erratic rainfall and severe oods, extended droughts, tropical cyclones or saline water intrusion, are making the situation worse. Smallholder farmers are amongst the most vulnerable to climate shocks. Lack of education and technical skills, poverty, risks inherent to agricultural investments, limited assets and Financial capital are major reasons for low investments in enhancing adaptive capacity. Now, technology could be the key to improving smallholder resilience to disasters and their opportunities for recovery.